Luminescence and Light-Driven Energy and Electron Transfer from an Exceptionally Long-Lived Excited State of a Non-Innocent Chromium(III) Complex - Treiling, Steffen; Wang, Cui; Foerster, Christoph; Reichenauer, Florian; Kalmbach, Jens; Boden, Pit; Harris, Joe P.; Carrella, Luca M.; Rentschler, Eva; Resch-Genger, Ute; Reber, Christian; Seitz, Michael; et al. (Angewandte Chemie International Edition, 2019)
Photoactive metal complexes employing Earth-abundant metal ions are a key to sustainable photophysical and photochemical applications. We exploit the effects of an inversion center and ligand non-innocence to tune the luminescence and photochemistry of the excited state of the [CrN6] chromophore [Cr(tpe)2]3+ with close to octahedral symmetry (tpe=1,1,1-tris(pyrid-2-yl)ethane). [Cr(tpe)2]3+ exhibits the longest luminescence lifetime (τ=4500 μs) reported up to date for a molecular polypyridyl chromium(III) complex together with a very high luminescence quantum yield of Φ=8.2 % at room temperature in fluid solution. Furthermore, the tpe ligands in [Cr(tpe)2]3+ are redox non-innocent, leading to reversible reductive chemistry. The excited state redox potential and lifetime of [Cr(tpe)2]3+ surpass those of the classical photosensitizer [Ru(bpy)3]2+ (bpy=2,2′-bipyridine) enabling energy transfer (to oxygen) and photoredox processes (with azulene and tri(n-butyl)amine).
CRIS-Team Scopus Importer:2023-03-27
Keywords: Earth-abundant metals; Laporte's rule; Luminescence; Photoredox chemistry; Sustainable Chemistry